Analysis of Public Participation in Covid-19 Handling Policies in Cibalongsari Village - Arini Nursyahban; Rahmat Hidayat; Indra Aditya; Evi Priyanti (Peneliti.net, 2022)
To achieve the success of a development, community participation is an important aspect. Because participation is the participation of a person or group of people in an activity that is carried out consciously. Sustainability of development results will not succeed if it is not supported by the role of the community. In an empowerment program, community participation must cover the entire process from the initial stage to the final stage. Sastropoetro said that the process of participation or participation describes personal involvement in the form of: (1) the decision-making process; (2) determine the desired needs; and (3) directing and realizing the goals and priorities to be achieved. In this concept it means that the needs and desires of the community to be achieved can be the encouragement or willingness of the community to participate in an empowerment program. In principle, every empowerment carried out by the community must always be improved in quality according to the wishes of the client (community) under it, but in reality this is not the case. One way to improve the quality of empowerment is to fulfill public complaints.